Collusion and technological determinism: the manager, his consultant's method and information technology. (18th January 2006) - MacDonald, Stuart
The paper combines two basic arguments. The first is that collusion cements the relationship between management consultant and hiring manager, often to the cost of the organisation that pays them both. One consequence is a developing dependency of the hiring manager on the management consultant and on the management method he offers. The second argument is that many of the management methods most popular over the last two decades have been determined by the exigencies of information technology rather than by the requirements of management. When the two arguments are put together, it is possible to associate the rise of IT with the decline in the ability of managers to manage. The paper explores this association and its implications.